Improving the understandability of the next edition of the International System of Units (SI) by focusing on its conceptual structure. (April 2017) - Mari, Luca; Blattner, Peter; Pavese, Franco
Highlights: The draft next edition of the International System of Units (SI) is presented. The complex structure of the definitions of units in the draft is analyzed. A simpler and more understandable structure is proposed and justified. Abstract: The International System of Units (SI) is fundamental for the social, and not only the scientific, role of metrology, and as such its understandability is a crucial issue. The SI is officially presented in a document commonly called the "SI Brochure", published by the International Bureau of Weights and Measures (BIPM). According to the current draft of the new SI Brochure, the next edition of the SI will be significantly more complex in its conceptual structure than the previous ones. Identifying a strategy for effectively communicating its main contents is then a worthwhile endeavor, in order to increase the acceptance and thus the sustainability of the SI itself. Our proposal is to focus on the structure of the definitions, while omitting all physical contents, which are inaccessible to most potential readers: this is instrumental to the awareness campaigns recommended by the General Conference on Weights and Measures (CGPM) to make the next edition of the SI understandable by a diverse readership without compromising scientific rigour. By unpacking the structural contents, the structure of definitions that we finally propose has the merit not only of being understandable, but also of highlighting the fundamental nature of metrology: a complex body of knowledge intertwining science and technology, society, and language even in its fundamental definitions.